ANALISIS DAMPAK KEBIJAKAN PROGRAM RUMAH DESA SEHAT (RDS) TERHADAP UPAYA PENURUNAN STUNTING DI NAGARI TARAM - Aprilian, Nia; Yusran, Rahmadani (Penerbit Lafadz Jaya, 2025)
Stunting is one of the major challenges in human resource development in Indonesia, with multidimensional impacts, particularly on early childhood. The government has introduced the Healthy Village Home Program (RDS) as a convergence platform for local development actors to accelerate stunting reduction. This study aims to analyze the impact of the RDS Program in Nagari Taram using Thomas R. Dye's (2017) five policy impact indicators: impact on target groups, spillover effects, short- and long-term impacts, direct costs, and indirect costs. This research applies a descriptive qualitative approach, with data collected through in-depth interviews, participatory observation, and document analysis. The findings indicate that the program has not yet achieved optimal impact due to limited behavioral transformation among target groups, weak integration of health messages into social life, fragile institutional continuity, and constrained resources. Recommendations include strengthening cross-sector coordination forums, family-based health literacy strategies, integration of health promotion messages into social activities, village budget advocacy, and incentive mechanisms to offset community participation burdens. The RDS program requires strategic and operational enhancement to generate meaningful and sustainable policy impacts in reducing stunting at the village level.